A high-performance atomic-level dispersed catalyst and its preparation method and application

By synthesizing the catalyst precursor at low temperature and performing alcohol washing, drying, and calcining, the problem of low dispersion of the existing catalyst activity center is solved, and a high-performance atomic-scale dispersion catalyst with high catalytic efficiency and performance is prepared.

CN119406412BActive Publication Date: 2025-04-29GUANGDONG INST OF NEW MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510026932.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-29
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing high-dispersion catalysts have problems with low dispersion of the active center and the catalytic efficiency and performance still need to be further improved.

Method used

By synthesizing the catalyst precursor at low temperature, using alcohol washing, drying, and calcining, a high-performance atomic-grade dispersion catalyst with small active center size and high dispersion is prepared.

Benefits of technology

The resulting catalyst has excellent catalytic efficiency and performance, uniform particle composition, adjustable components, high dispersion and high loading, and is suitable for energy and chemical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406412B_ABST
    Figure CN119406412B_ABST
Patent Text Reader

Abstract

The present invention provides a high-performance atomic-level dispersed catalyst and a preparation method and application thereof, the preparation method comprising the following steps: S1. uniformly dispersing a metal salt into an organic aqueous solution to obtain a metal salt solution, placing it at a low temperature of 20 to 80°C for standby use; S2. placing a carrier into an alkaline organic aqueous solution to obtain an alkaline solution, placing it at a low temperature, and keeping the same temperature as the metal salt solution obtained in S1 for standby use; S3. under the condition of maintaining a low temperature, slowly dropping the metal salt solution into the alkaline solution, while supplementing the alkaline solution, generating a suspension, adjusting the pH value to the pH value range of metal ion precipitation, aging for 1.5 to 2.5 hours, naturally warming to room temperature, washing with alcohol, drying, and calcining to obtain the high-performance atomic-level dispersed catalyst. The high-performance atomic-level dispersed catalyst has a small active center size, high dispersion, excellent catalytic efficiency and performance, simple method operation, strong controllability, and broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic chemical synthesis, and in particular to a high-performance atomic-level dispersed catalyst and a preparation method and application thereof. Background Art

[0002] Catalysts are known as chemical "chips" that can improve the efficiency of chemical reactions and promote large-scale production. Chemical synthesis, petrochemical refining, and environmental treatment are its three main application scenarios. The catalytically active components of precious metal catalysts are mainly platinum (Pt), palladium (Pd), etc., which are representatives of high-efficiency and stable catalysts, but the scarcity of precious metal materials is extremely serious. In 2021, the global reserves of platinum group metals were about 70,000 tons, and my country had only 401 tons. At the same time, due to the scarcity of precious metals, high costs restrict some of their applications in catalysts. For this reason, non-precious metal catalysts represented by Fe, Co, and Ni have been proven to be the best catalysts for many catalytic reactions (thermal catalysis, electrocatalysis, and photocatalysis) due to their high intrinsic activity, low cost, easy generation of active substances, and easy adjustment of structure. However, the catalytic activity and stability of non-precious metal active components such as single metal nickel are still difficult to meet the needs, and the reaction kinetics still need to be improved. Therefore, it is urgent to develop new high-catalytic performance catalysts.

[0003] Catalyst performance is closely related to the dispersion and size of active centers. The dispersion and size of the active centers of a catalyst have a significant impact on its performance. Specifically, the higher the dispersion of the active centers, the higher the catalytic efficiency of the catalyst is generally, because more active centers are exposed to the reactants, increasing the possibility of reaction. In addition, the size of the active center also affects the performance of the catalyst. A smaller active center size generally means a higher specific surface area, thereby providing more active sites, which is conducive to improving catalytic efficiency. Therefore, atomically dispersed catalysts with high dispersion are of great strategic significance to energy and chemical industry.

[0004] Chinese patent CN117895016A "A supported noble metal nanocatalyst and its preparation method" discloses a supported noble metal nanocatalyst, which uses rapid freezing to solidify the mixed slurry to prevent the agglomeration and segregation of the metal precursor on the carrier surface during the freezing process, and achieves the preparation of a catalyst with high loading, high dispersion, narrow particle size distribution, and few harmful impurities. However, it only reduces the agglomeration and segregation of the metal precursor on the carrier surface by solidifying the slurry, and does not improve the dispersion of the active center. Its catalytic efficiency and performance still need to be further improved.

[0005] Therefore, it is of great significance to provide a high-performance atomic-level dispersed catalyst with high dispersion of active centers, excellent catalytic efficiency and performance, and a preparation method and application thereof. Summary of the invention

[0006] In view of the fact that the existing highly dispersed catalysts have low dispersion of active centers, and the catalytic efficiency and performance still need to be further improved, the present invention provides a high-performance atomic-level dispersed catalyst and a preparation method and application thereof. The catalyst precursor is synthesized in solution at low temperature, and then washed with alcohol, dried, and calcined to obtain a product. The obtained high-performance atomic-level dispersed catalyst has small active center size, high dispersion, excellent catalytic efficiency and performance, simple operation, strong controllability, and has broad application prospects.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a high-performance atomic-level dispersed catalyst comprises the following steps:

[0009] S1. Disperse the metal salt evenly into the organic aqueous solution to obtain a metal salt solution, and place it at a low temperature of -20~-80℃ for standby use;

[0010] S2. placing the carrier in an alkaline organic aqueous solution to obtain an alkaline solution, placing it at a low temperature of -20~-80°C, maintaining the same temperature as the metal salt solution obtained in S1, and set aside;

[0011] S3. Under the condition of maintaining the same temperature as S1 and S2 at -20~-80°C, slowly adding the metal salt solution to the alkaline solution, while replenishing the alkaline solution to generate a suspension, adjusting the pH value to the pH range of metal ion precipitation, aging for 1.5~2.5h, naturally warming to room temperature, washing with alcohol, drying, and calcining to obtain the high-performance atomic-level dispersed catalyst;

[0012] The metal salt in S1 includes one or more of platinum salt, rhodium salt, iridium salt, gold salt, iron salt, cobalt salt and nickel salt;

[0013] S1 The organic aqueous solution includes one or more of an acetone aqueous solution, an ethanol aqueous solution, a methanol aqueous solution, and a glycerol aqueous solution;

[0014] S2 The carrier is a 3D printed catalyst carrier.

[0015] Furthermore, the metal salt in S1 includes one or more of nitrate, acetate, and chloride.

[0016] Furthermore, the low temperature in S1, S2 and S3 is achieved by cooling the solution in a liquid nitrogen solution to a desired temperature.

[0017] Furthermore, the alkaline organic aqueous solution in S2 is a solution obtained by diluting an alkaline solution with deionized water and an organic solvent in proportion; the alkaline solution is one or more of ethylenediamine solution, ammonia solution, and urea solution; the organic solvent includes one or more of acetone, ethanol, methanol, and glycerol; the ratio is alkaline solution: deionized water: organic solvent = (1~5):1:(1~8).

[0018] Furthermore, the slow dripping in S3 is to slowly drip the metal salt solution into the alkaline solution through a peristaltic pump.

[0019] Another object of the present invention is to provide a high-performance atomically dispersed catalyst.

[0020] A high-performance atomic-level dispersed catalyst is prepared according to any of the above-mentioned methods for preparing a high-performance atomic-level dispersed catalyst.

[0021] Another object of the present invention is to provide an application of a high-performance atomic-level dispersed catalyst.

[0022] A use of the high-performance atomically dispersed catalyst described above in a catalyst.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] The high-performance atomic-level dispersed catalyst provided by the present invention is obtained by cooling a metal salt and a carrier at a low temperature, and then slowly dropping a metal salt solution into a carrier solution while maintaining the low temperature, so as to be formed in an ultra-low temperature environment. Under the ultra-low temperature condition, the diffusion coefficients of ions and atoms are reduced, resulting in an increase in nucleation performance and slow grain growth, thereby generating an atomic-level dispersed metal catalyst. The obtained catalyst particles have a small size, a small active center size, and are evenly dispersed, and can provide a larger specific surface area and more active sites. The catalyst particles have uniform composition, adjustable components, high dispersion, high loading capacity, excellent catalytic efficiency and performance, simple operation, strong controllability, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0026] Figure 1 This is a characterization test result diagram of the high-performance atomically dispersed catalyst in Example 1 of the present application.

[0027] Figure 2 This is a TEM image of the high-performance atomically dispersed catalyst of Example 1 of the present application.

[0028] Figure 3 This is a TEM image of the catalyst obtained in Comparative Example 1 of the present application.

[0029] Figure 4 This is a TEM image of the catalyst obtained in Comparative Example 2 of the present application.

[0030] Figure 5 This is a TEM image of the catalyst obtained in Comparative Example 3 of the present application. DETAILED DESCRIPTION

[0031] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0032] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0033] Embodiment 1: A method for preparing a high-performance atomically dispersed catalyst comprises the following steps:

[0034] S1. Evenly disperse nickel nitrate in an acetone aqueous solution, slightly heat and stir until completely dissolved, and cool to room temperature to obtain a nickel nitrate solution, which is placed in liquid nitrogen at -50°C for standby use;

[0035] S2. Dilute ammonia water with deionized water and acetone in a ratio of 1:1:1, stir evenly to obtain an alkaline organic aqueous solution, place the 3D printed catalyst carrier in the alkaline organic aqueous solution to obtain an alkaline solution, cool it in liquid nitrogen, place it at a low temperature, and keep it at the same temperature of -50°C as the nickel nitrate solution obtained in S1 for use;

[0036] S3. While maintaining a low temperature of -50°C, slowly add the nickel nitrate solution to the alkaline solution through a peristaltic pump, and at the same time replenish the alkaline solution to generate a suspension, and adjust the pH value to greater than 10. After the titration is completed, mature for 2 hours, then naturally heat to room temperature, wash with alcohol, dry, and calcine to obtain the high-performance atomic-level dispersed catalyst.

[0037] Embodiment 2: A method for preparing a high-performance atomically dispersed catalyst comprises the following steps:

[0038] S1. Disperse nickel acetate evenly in an ethanol aqueous solution, heat and stir slightly until completely dissolved, cool to room temperature to obtain a nickel acetate solution, place it in liquid nitrogen, and place it at -40°C for standby use;

[0039] S2. Dilute the ethylenediamine solution with deionized water and ethanol in a ratio of 2:1:7, stir evenly, and obtain an alkaline organic aqueous solution. Place the 3D printed catalyst support in the alkaline organic aqueous solution to obtain an alkaline solution, cool it in liquid nitrogen, and place it at a low temperature to keep the same temperature as the nickel acetate solution obtained in S1 at -40°C for standby use;

[0040] S3. While maintaining a low temperature of -40°C, slowly add the nickel acetate solution to the alkaline solution through a peristaltic pump, and at the same time replenish the alkaline solution to generate a suspension, and adjust the pH value to be greater than 12. After the titration is completed, mature for 2 hours, then naturally heat to room temperature, wash with alcohol, dry, and calcine to obtain the high-performance atomic-level dispersed catalyst.

[0041] Embodiment 3: A method for preparing a high-performance atomically dispersed catalyst comprises the following steps:

[0042] S1. Disperse cobalt chloride evenly in an ethanol aqueous solution, heat and stir slightly until completely dissolved, cool to room temperature to obtain a cobalt chloride solution, place it in liquid nitrogen, and place it at -30°C for standby use;

[0043] S2. Dilute ammonia water with deionized water and ethanol in a ratio of 5:1:5, stir evenly to obtain an alkaline organic aqueous solution, place the 3D printed catalyst support in the alkaline organic aqueous solution to obtain an alkaline solution, cool it in liquid nitrogen, place it at a low temperature, and keep the same temperature as the cobalt chloride solution obtained in S1 at -30°C for standby use;

[0044] S3. While maintaining a low temperature of -30°C, the cobalt chloride solution is slowly added to the alkaline solution through a peristaltic pump, and the alkaline solution is supplemented at the same time to generate a suspension, and the pH value is adjusted to be greater than 9. After the titration is completed, it is aged for 2 hours, and then naturally heated to room temperature, washed with alcohol, dried, and calcined to obtain the high-performance atomic-level dispersed catalyst.

[0045] Example 4: A method for preparing a high-performance atomically dispersed catalyst, comprising the following steps:

[0046] S1. Disperse cobalt nitrate evenly in an ethanol aqueous solution, heat and stir slightly until completely dissolved, cool to room temperature to obtain a cobalt nitrate solution, place it in liquid nitrogen, and place it at a low temperature of -65°C for standby use;

[0047] S2. Dilute the ethylenediamine solution with deionized water and ethanol in a ratio of 4:1:8, stir evenly to obtain an alkaline organic aqueous solution, place the 3D printed catalyst support in the alkaline organic aqueous solution to obtain an alkaline solution, cool it in liquid nitrogen, place it at a low temperature, and keep it at the same temperature of -65°C as the cobalt nitrate solution obtained in S1 for use;

[0048] S3. While maintaining a low temperature of -65°C, the cobalt nitrate solution is slowly added to the alkaline solution through a peristaltic pump, and the alkaline solution is supplemented at the same time to generate a suspension, and the pH value is adjusted to be greater than 9. After the titration is completed, it is aged for 2 hours, and then naturally heated to room temperature, washed with alcohol, dried, and calcined to obtain the high-performance atomic-level dispersed catalyst.

[0049] Comparative Example 1: A method for preparing a catalyst, comprising the following steps:

[0050] S1. Evenly disperse nickel nitrate in an acetone aqueous solution, heat and stir slightly until completely dissolved, cool to room temperature to obtain a nickel nitrate solution, place at 25°C for standby use;

[0051] S2. Dilute ammonia water with deionized water and acetone in a ratio of 1:1:1, stir evenly to obtain an alkaline organic aqueous solution, place the 3D printed catalyst support in the alkaline organic aqueous solution to obtain an alkaline solution, and keep the same temperature of 25°C as the nickel nitrate solution obtained in S1 for standby use;

[0052] S3. The nickel nitrate solution is slowly added to the alkaline solution through a peristaltic pump, and the alkaline solution is supplemented at the same time to form a suspension, and the pH value is adjusted to be greater than 10. After the titration is completed, it is aged for 2 hours, washed with alcohol, dried, and calcined to obtain the catalyst.

[0053] Compared with Example 1, the main difference of this comparative example is that the catalyst synthesis is carried out at room temperature.

[0054] Comparative Example 2: A method for preparing a catalyst, comprising the following steps:

[0055] S1. Evenly disperse nickel nitrate in an acetone aqueous solution, slightly heat and stir until completely dissolved, and cool to room temperature to obtain a nickel nitrate solution, which is placed in liquid nitrogen at a low temperature of -10°C for standby use;

[0056] S2. Dilute ammonia water with deionized water and acetone in a ratio of 1:1:1, stir evenly to obtain an alkaline organic aqueous solution, place the 3D printed catalyst carrier in the alkaline organic aqueous solution to obtain an alkaline solution, cool it in liquid nitrogen, place it at a low temperature, and keep it at the same temperature of -10°C as the nickel nitrate solution obtained in S1 for use;

[0057] S3. While maintaining a low temperature of -10°C, slowly add the nickel nitrate solution to the alkaline solution through a peristaltic pump, and at the same time replenish the alkaline solution to generate a suspension, and adjust the pH value to greater than 10. After the titration is completed, mature for 2 hours, then naturally heat to room temperature, wash with alcohol, dry, and calcine to obtain the catalyst.

[0058] Compared with Example 1, the main difference of this comparative example is that the catalyst synthesis temperature is -10°C.

[0059] Comparative Example 3: A method for preparing an atomically dispersed catalyst, comprising the following steps:

[0060] S1. The nickel nitrate is evenly dispersed in an acetone aqueous solution, slightly heated and stirred until completely dissolved, and cooled to room temperature to obtain a nickel nitrate solution for standby use;

[0061] S2. Dilute ammonia water with deionized water and acetone in a ratio of 1:1:1, stir evenly to obtain an alkaline organic aqueous solution, place the 3D printed catalyst support in the alkaline organic aqueous solution to obtain an alkaline solution for standby use;

[0062] S3. The nickel nitrate solution is slowly added to the alkaline solution through a peristaltic pump, and the alkaline solution is supplemented at the same time to form a suspension, and the pH value is adjusted to be greater than 10. After the titration is completed, the suspension temperature is reduced to -50°C and aged for 2 hours, followed by alcohol washing, drying, and calcination to obtain the catalyst.

[0063] Compared with Example 1, the main difference of this comparative example is that the synthesis temperature of the catalyst is room temperature.

[0064] Example 1 was characterized and tested, and the results were as follows Figure 1 , Figure 2 shown. Figure 1 is a characterization test result diagram of the high performance atomically dispersed catalyst of Example 1 of the present application, Figure 1 It can be seen that the high-performance atomic-level dispersed catalyst sample obtained in the present application has a large number of wrinkled structures, presents a flower-like morphology, the metal particles are highly dispersed, evenly distributed, and the active component loading is high, indicating that the high-performance atomic-level dispersed catalyst obtained in the present application has uniform composition, high dispersion, high loading, and excellent catalytic efficiency and performance. Figure 2 is a TEM image of the high performance atomically dispersed catalyst of Example 1 of the present application, Figure 2 It can be seen that the high-performance atomic-level dispersed catalyst sample obtained in the present application has small particle size, is evenly dispersed, and has no agglomeration phenomenon, indicating that the high-performance atomic-level dispersed catalyst obtained in the present application has small particle size, small active center size, and is evenly dispersed, which can provide a larger specific surface area and more active sites, and has excellent catalytic efficiency and performance.

[0065] The test results of the other embodiments are basically consistent with it.

[0066] Figure 3 This is a TEM image of the catalyst obtained in Comparative Example 1 of the present application. The catalyst synthesis in Comparative Example 1 was carried out at room temperature, and the size of the obtained catalyst particles was about 60-200 nm, and the particles were agglomerated, with poor catalytic efficiency and performance.

[0067] Figure 4This is a TEM image of the catalyst obtained in Comparative Example 2 of the present application. The catalyst synthesis temperature in Comparative Example 2 is -10°C, and the size of the obtained catalyst particles is about 10 nanometers, which is relatively large, and the dispersion is poor, and the catalytic efficiency and performance are not high.

[0068] Figure 5 This is a TEM image of the catalyst obtained in Comparative Example 3 of the present application. The synthesis temperature of the catalyst in Comparative Example 3 is room temperature, and then the mixed slurry is transferred to -50°C for curing. However, during its synthesis, the catalyst ion diffusion coefficient is large, the nucleation potential energy is low, the grain growth rate is fast, and the particles are easy to agglomerate, and the catalytic efficiency and performance of the obtained catalyst are poor.

[0069] The above samples were subjected to performance tests, and the experimental test methods were as follows:

[0070] The catalyst obtained above was pressed into tablets at 10MPa, and after crushing, 20-40 mesh particles were taken for methane carbon dioxide reforming reaction performance test. The reaction was carried out in a fixed bed microreactor (reaction tube inner diameter 6mm), 0.1g of the above catalyst was weighed and loaded into the reaction tube, hydrogen was passed under normal pressure, and the temperature was programmed to 800℃ for reduction, with a hydrogen flow rate of 30mL / min; after the multi-layer core-shell structure nickel-based catalyst was reduced, hydrogen was switched to feed gas (Ar / CH4 / CO2=4 / 48 / 48), with a flow rate of 35mL / min, GHSV=21000mL·g -1 ·h -1 The reaction was carried out at 800° C. The reaction products were analyzed online by gas chromatography GC (SP-2100A)-thermal conductivity detector TCD.

[0071] The test results of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in the following table:

[0072] Table 1 Test results of Examples 1 to 3 and Comparative Examples 1 to 3

[0073]

[0074] As can be seen from Table 1, the high-performance atomic-level dispersed catalysts obtained by the present invention have excellent catalytic efficiency and performance. The initial conversion rates of Examples 1-3 are all higher than 90%, and after a long reaction of 60 hours, they still have a methane conversion rate of not less than 85%. The catalyst synthesis of Comparative Example 1 is carried out at room temperature, and the initial conversion rate is lower than 80%. After 10 hours of reaction, the methane conversion rate has dropped to 42%, and the catalytic efficiency and performance are poor; the catalyst synthesis temperature of Comparative Example 2 is -10°C, and the initial conversion rate is better in the comparative example, but after a long reaction of 60 hours, the methane conversion rate drops rapidly to 50%, the stability is general, the cycle performance is low, and the catalytic performance is poor; while the synthesis temperature of Comparative Example 3 is room temperature, and then transferred to -50°C to solidify the mixed slurry, the actual catalytic performance is close to that of Comparative Example 1 synthesized at room temperature, the initial conversion rate is only 76%, and it has dropped to 45% after 10 hours of reaction, and the catalytic efficiency and performance are poor.

[0075] In summary, the present invention cools the metal salt and the carrier at low temperature and then slowly drops the metal salt solution into the carrier solution while maintaining the low temperature, so as to form a high-performance atomic-level dispersed catalyst in an ultra-low temperature environment. The obtained catalyst particles have a small size, a small active center size, and are evenly dispersed, and can provide a larger specific surface area and more active sites. The catalyst particles have uniform composition, adjustable components, high dispersion, high loading capacity, and excellent catalytic efficiency and performance. The method is simple to operate, has strong controllability, and has broad application prospects.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-performance atomically dispersed catalyst, characterized in that: The following steps are involved: S1. Disperse the metal salt evenly into the organic aqueous solution to obtain a metal salt solution, and place it at a low temperature of -20~-80℃ for standby use; S2. placing the carrier in an alkaline organic aqueous solution to obtain an alkaline solution, placing it at a low temperature of -20~-80°C, maintaining the same temperature as the metal salt solution obtained in S1, and set aside; S3. Under the condition of maintaining the same temperature as S1 and S2 at -20~-80°C, slowly adding the metal salt solution to the alkaline solution, while replenishing the alkaline solution to generate a suspension, adjusting the pH value to the pH range of metal ion precipitation, aging for 1.5~2.5h, naturally warming to room temperature, washing with alcohol, drying, and calcining to obtain the high-performance atomic-level dispersed catalyst; The metal salt in S1 includes one or more of platinum salt, rhodium salt, iridium salt, gold salt, iron salt, cobalt salt and nickel salt; S1 The organic aqueous solution includes one or more of an acetone aqueous solution, an ethanol aqueous solution, a methanol aqueous solution, and a glycerol aqueous solution; S2 The carrier is a 3D printed catalyst carrier; The slow dripping in S3 is to slowly drip the metal salt solution into the alkaline solution through a peristaltic pump.

2. A method for preparing a high-performance atomically dispersed catalyst according to claim 1, characterized in that: S1 The metal salt includes one or more of nitrate, acetate and chloride.

3. A method for preparing a high-performance atomically dispersed catalyst according to claim 1, characterized in that: The low temperature described in S1, S2 and S3 is achieved by cooling the solution in a liquid nitrogen solution to a desired temperature.

4. A method for preparing a high-performance atomically dispersed catalyst according to claim 1, characterized in that: S2 The alkaline organic aqueous solution is a solution obtained by diluting an alkaline solution with deionized water and an organic solvent in proportion; the alkaline solution is one or more of ethylenediamine solution, ammonia solution, and urea solution; the organic solvent includes one or more of acetone, ethanol, methanol, and glycerol; the ratio is alkaline solution: deionized water: organic solvent = (1~5):1:(1~8).

5. Use of a high-performance atomically dispersed catalyst prepared by the method for preparing a high-performance atomically dispersed catalyst according to any one of claims 1 to 4 in a methane carbon dioxide reforming reaction.

Citation Information

Patent Citations

  • Supported noble metal nano-catalyst and preparation method thereof

    CN117895016A

  • Method for obtaining atomic-scale dispersed noble metal catalyst by one-step reduction loading

    CN110404531A

  • Cobalt-based monoatomic dehydrogenation catalyst and method for preparing olefin corresponding to paraffin from paraffin by using same

    CN112996596A